Antagonism of nonaflatoxigenic Aspergillus flavus isolated from peanuts against aflatoxigenic A. flavus growth and aflatoxin B1 production in vitro - Rahman, Mohd Azuar Hamizan; Selamat, Jinap; Samsudin, Nik Iskandar Putra; Shaari, Khozirah; Mahror, Norlia; John, Joshua Mark (John Wiley & Sons, 2022)
Aspergillus section Flavi constitutes several species of opportunistic fungi, notable among them are A. flavus and A. parasiticus, capable of surviving harsh conditions and colonizing a wide range of agricultural products pre- and postharvest. Physical and chemical control methods are widely applied in order to mitigate the invasion of A. flavus in crops. However, physical control is not suitable for large scale and chemical control often leads to environmental pollution, whereas biological control offers a safer, environmentally friendly, and economical alternative. The present study aimed to investigate the antagonism of several non-aflatoxigenic A. flavus strains against the aflatoxigenic ones in vitro (semisynthetic peanut growth medium; MPA) in terms of colony growth rate and AFB1 inhibition. Different peanut concentrations were used to obtain the optimum peanut concentration in the formulated growth medium. A dual culture assay was performed to assess the antagonism of nonaflatoxigenic strains against the aflatoxigenic ones. Results revealed that 9% MPA exhibited the highest growth and AFB1 inhibition by nonaflatoxigenic strains. It was also found that different nonaflatoxigenic strains exhibited different antagonism against the aflatoxigenic ones which ranged from 11.09 ± 0.65% to 14.06 ± 0.14% for growth inhibition, and 53.97 ± 2.46% to 72.64 ± 4.54% for AFB1 inhibition. This variability could be due to the difference in antagonistic metabolites produced by different nonaflatoxigenic strains assessed in the present study. Metabolomics study to ascertain the specific metabolites that conferred the growth and aflatoxin inhibition is ongoing.